2011
DOI: 10.1097/scs.0b013e31820f7fac
|View full text |Cite
|
Sign up to set email alerts
|

Management of an Exposed Mandibular Plate After Fibula Free Flap With Vacuum-Assisted Closure System

Abstract: This therapy is a safe, innovative, and useful tool and can be of great assistance especially in complex craniofacial wounds, but it poses some problems such as intricate contours and orifices of the head and neck region, painful dressing changes, and remarkable costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“… 3 Another case of mandibular osteoradionecrosis reported use of NPWT before definitive reconstruction. 4 Forehead defects with full-thickness tissue loss showed granulation formation with NPWT followed by surgical closure. 5 Four retrospective reviews of 112 patients with 73 H&N wounds demonstrated improved wound healing without complication.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Another case of mandibular osteoradionecrosis reported use of NPWT before definitive reconstruction. 4 Forehead defects with full-thickness tissue loss showed granulation formation with NPWT followed by surgical closure. 5 Four retrospective reviews of 112 patients with 73 H&N wounds demonstrated improved wound healing without complication.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, multiple studies have identified that skin thinning and necrosis can occur following mandibular plating, resulting in exposure of titanium plates as a complication of the plating technique for mandibular defects . Therefore, optimal reconstruction includes not only rigid fixation that can withstand force and fatigue, but also aesthetic recapitulation of the original anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…NPWT has been used extensively in the treatment of acute and chronic wounds on the torso and limbs, and has been used to treat diabetic foot ulcers [ 4 , 5 , 6 , 7 ]. However, NPWT has been under utilized in head and neck surgeries, despite several case studies showing safe and effective use of NPWT [ 8 , 9 , 10 ]. The current manuscript will briefly review the history of wound healing, the basic science behind NPWT, the considerations for maxillofacial applications, and future improvements for NPWT.…”
Section: Introductionmentioning
confidence: 99%